PENILAIAN AUTENTIK - Mona Vebyani; Khofifah Choirun Nisya Siregar; Mariam Nasution (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Assessment in elementary schools has tended to focus solely on cognitive aspects, thus failing to fully reflect students' competencies. This paper aims to examine the concept, characteristics, and techniques of authentic assessment as a comprehensive evaluation paradigm in elementary education. Through a literature review, it was found that authentic assessment holistically assesses three competency domains: knowledge, skills, and attitudes. It utilizes a variety of techniques such as performance assessment, projects, portfolios, observations, and written and oral tests. Its key characteristics include an orientation toward actual performance, continuous implementation, integration with the learning process, and relevance to everyday life contexts. Authentic assessment shifts the evaluation paradigm from merely measuring